Test book on physical rehabilitation and sports medicine - Malakhova, S. N.; Cherepok, A. A.; Tkalich, I. V.; Малахова, Світлана Миколаївна; Черепок, Олександр Олексійович; Ткаліч, Ігор Вячеславович (Запорізький державний медичний університет, 2016)
Test book compiled based on the current curriculum and programs for educational discipline "Physical Rehabilitation and Sports Medicine" for medical students in higher educational institutions III-IV levels of accreditation for training areas "Medicine" in 1201, for specialties 7.12010001 "Medicine" 7.12010002 "Pediatrics" according to educational qualification characteristics and educational and vocational training programs approved by the Ministry of Health of Ukraine orders from 08.07.10 № 539 «On Amendments to the curriculum training educational qualification level "specialist"qualifications"doctor"in higher educational institutions of the fourth level in the field"Medicine","Pediatrics","Medical prophylaxis", approved by the Ministry of Health 19.10 .2009 № 749». Test book is intended for independent work of students of medical faculties IV course in preparation for the practical training in the discipline "Physical rehabilitation and sports medicine." Test book discussed and approved at a meeting of the Cyclic Methodical Committee from Therapeutic Disciplines of Zaporozhye State Medical University and recommended for publication by the Central Methodical Council of Zaporozhye State Medical University (the record No 2 as of 24.11.16).